SPESIALISASI AUDITOR SEBAGAI VARIABEL PEMODERASI PENGARUH AUDIT TENURE DAN PERGANTIAN AUDITOR PADA AUDIT DELAY - Ratnaningsih, Ni Made Dwita; Dwirandra, A.A N.B (E-Jurnal Akuntansi, 2016)
Public accountan firm (PAF) commitment with the company as a client, makes PAF or auditors have a specific knowledge of the operational companies. This study aimed to analyze the factors auditor’s commitment (audit tenure), auditor change in the audit delay with specialization moderated by the auditors in companies listed in Indonesia Stock Exchange 2009-2014. Samples were obtained by purposive sampling of 141 companies listed on the Stock Exchange which reported the audited financial statements for 2009-2014. This study uses analysis techniques Moderating Regression Analysis (MRA), with SPSS 13.0. These results indicate that the specialization of auditors moderate the effect of audit tenure and auditor change. Audit tenure moderated to produce shorter audit delay. Specialization auditor is able to weaken the relationship auditor changr in the audit delay. Partially audit auditor tenure and auditor specialization negative effect on audit delay, and the change of auditor positive effect on audit delay.
Keywords: audit delay, audit tenure, change auditor, and auditor specialization